Market analysis and value perception of agronomic services - DeTurk, Jarod R. (Kansas State University, 2022)
There has been a push towards producing food more sustainably. This is a global trend and is important for every industry. Agronomic principals have a unique place in agriculture. There are sustainable practices that farmers can implement, that equipment producers can develop for farmers, but agronomy can bring together multiple parts of production. Agronomy focuses on soil health, fertility, pesticide applications, and other facets of production so it is in a position to align technical goals of multiple parts of production to satisfy ever changing global needs. Though it appears that the importance of agronomy in production agriculture is increasing, there is little research on the producer value of agronomic services, and what makes a producer employ a specialized agronomist in their operation. This research focuses on those issues. The study is conducted through a questionnaire to producers that asks questions ranging from demographic information to operation information, and finally focusing on whether a producer employs an agronomist in some capacity and what benefits that producer receives from that decision. The results of the questionnaire are used to estimate a logit regression to determine factors that influence a producer’s decision to employ an agronomist, and descriptive statistics on producer’s value perceptions of how much value they receive from employing an agronomist. These results are beneficial both to the agronomic industry in terms of tailoring what is offered in agronomic services, and are valuable to producers interested in seeing a more quantitative approach to what influences their peers’ decisions. The results show that if a producer has a higher percentage of crops as their primary income stream, they are less likely to hire an agronomist. Inversely, if a producer is spread between producing multiple agricultural products or has off-farm income they are more likely to employ an agronomist. It was originally thought that as an operation increased in size, hiring a specialized agronomist would be more likely, but the results are counter to this hypothesis. Over 50% of producers who completed the questionnaire employed an agronomist. Demographics such as education level and age had less effect on whether they employed a crop consultant than other independent variables that are particular to their operation. The value that producers employing an agronomist saw in those services came primarily from weed and other pest management, fertility, and input cost savings. Producers saw less value for an outside opinion or expertise, adverse conditions reporting such as poor weather, and other.
Keywords: Value add; Agronomy; Income; Agribusiness